2009
DOI: 10.1183/09031936.00023208
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein and unrecognised sleep-disordered breathing in the elderly

Abstract: Elevated levels of C-reactive protein (CRP) have been reported in patients with sleep-disordered breathing (SDB) and may represent an inflammatory marker of cardiovascular risk. However, the association of CRP with SBD in presumed healthy elderly subjects is unknown.In total, 851 (58.5% females) 68-yr-old subjects, who were free of any known cardiac or sleep disorders, were prospectively examined. Subjects underwent unattended polygraphy, and the apnoea/hypopnoea index (AHI) and oxyhaemoglobin desaturation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
3
11
0
1
Order By: Relevance
“…In this study, we found that CRP levels in the OSA patients were significantly higher as compared with that in normal individuals. Furthermore, significant differences in CRP levels were detected between mild and severe OSA patients, similar to findings by Roche et al (2009). Previous studies have also found that plasma CRP and IL-6 levels were elevated in patients with OSA.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that CRP levels in the OSA patients were significantly higher as compared with that in normal individuals. Furthermore, significant differences in CRP levels were detected between mild and severe OSA patients, similar to findings by Roche et al (2009). Previous studies have also found that plasma CRP and IL-6 levels were elevated in patients with OSA.…”
Section: Discussionsupporting
confidence: 76%
“…Elevated serum hs-CRP levels have also been reported in OSA patients in previous studies [4,5,13,17,19,27,28]. However, as will be discussed, there are conflicting results regarding hs-CRP levels in OSA patients.…”
Section: Discussionmentioning
confidence: 66%
“…Increased plasma IL-6 and CRP levels have been noted during hypoxic conditions, and IL-6 is one of the key regulators of CRP synthesis by the liver. Thus, hypoxia may contribute to elevated CRP levels in patients with OSA [5,27]. In other words, it appears that inflammation increases with the severity of OSA.…”
Section: Discussionmentioning
confidence: 92%
“…Various mechanisms link OSA to an increase in vascular diseases [6][7][8][9].These mechanisms can produce endothelial dysfunction, an early indicator of vascular disease. This is of great epidemiological importance, as it can favour or accelerate the process of atherogenesis and the development of cardiovascular disease [6,8,10,11].…”
mentioning
confidence: 99%
“…This is of great epidemiological importance, as it can favour or accelerate the process of atherogenesis and the development of cardiovascular disease [6,8,10,11].…”
mentioning
confidence: 99%